An evaluative framework for inclusive agricultural value chain policies and interventions – case: Mali - Michalscheck, Mirja; Ekpe, S.; Zemadim, Birhanu; Mabhaudhi, Tafadzwanashe; Minh, Thai Thi (Elsevier, 2024)
Advancing food security requires multi-level and inclusive approaches. This article presents a novel framework to (E) evaluate the social inclusiveness of policies and interventions (PIs) towards (V) vulnerable social groups in (A) agricultural value chains. The EVA-framework is applicable to any value chain, geography and vulnerable group. We apply it to the irrigated vegetable value chain of Mali, analyzing the social inclusiveness of weighted PIs towards women and youth. We find that respective PI formulation in Mali is largely not inclusive. Only few PIs set specific targets, quotas or a financial budget for women and youth inclusion. To be inclusive PIs need to consult targeted social groups, include clear targets, budgets, and accountability mechanisms, and be monitored and evaluated.